A Highly Sensitive Sensor Based on Reduced Graphene Oxide, Carbon Nanotube and a Co(II) Complex Modified Carbon Paste Electrode: Simultaneous Determination of Isoprenaline, Captopril and Tryptophan. Issue 12 (16th July 2015) - Rajabzadeh, Nooshin; Benvidi, Ali; Mazloum‐Ardakani, Mohammad; Firouzabadi, Afsaneh Dehghani; Vafazadeh, Rasoul
Abstract: This paper describes the development of a reduced graphene oxide (RGO), carbon nanotube (CNT) and Co(II) complex (cobalt(II) bis (benzoylacetone) ethylenediimino) (CBE) modified carbon paste electrode (CPE) for simultaneous determination of isoprenaline (IP), captopril (CAP) and tryptophan (Try). A pair of well‐defined redox peaks of Co(II) complex were obtained through a direct electron transfer between the Co(II) complex and the CPE. The proposed sensor showed very efficient electrocatalytic activity for anodic oxidation of IP in a 0.1 M phosphate buffer solution (pH 7.0). Square wave voltammetry (SWV) exhibited two linear dynamic ranges of 0.125–30.0 µM and 30.0–300.0 µM for IP. The detection limit for IP was found to be 50 nM. The proposed sensor was successfully applied for the determination of IP in real samples such as human blood serum, urine and IP ampoule. Abstract :